One-Pot Syntheses and Characterization of Group VI Carbonyl NHC Coordination Compounds - Zala Stopar; Evelin Gruden; Melita Tramšek; Gašper Tavčar (Molecules)
The reactions of N-heterocyclic carbenes (IMesNHC and IPrNHC) with transition metal carbonyls of group VI (Cr(CO)6, Mo(CO)6, and W(CO)6) were carried out in acetonitrile in simple one-pot syntheses and led to the formation of the coordination compounds IMesNHC–Cr(CO)5 (1a), IMesNHC–Mo(CO)5 (2a), IMesNHC–W(CO)5 (3a), IPrNHC–Cr(CO)5 (1b), IPrNHC–Mo(CO)5 (2b), and IPrNHC–W(CO)5 (3b). With the exception of 1b, the coordination compounds were formed selectively and in high yields. The method represents an effective and easy-to-perform alternative to the previously described methods for NHC–M(CO)5 (M = Cr, Mo, W). All prepared compounds were characterized by NMR and Raman spectroscopy. Compounds 1a, 2a, 3a, and 2b were also crystallized and structurally characterized by X-ray structure analysis. Finally, the structural features of all compounds were compared with DFT calculations of structurally optimized coordination compounds.